Novel insights of dietary polyphenols and obesity - Wang, Shu; Moustaid-Moussa, Naima; Chen, Lixia; Mo, Huanbiao; Shastri, Anuradha; Su, Rui; Bapat, Priyanka; Kwun, InSook; Shen, Chwan-Li (The Journal of nutritional biochemistry, 2014)
The prevalence of obesity has steadily increased over the past three decades both in the United States and worldwide. Recent studies have shown the role of dietary polyphenols in the prevention of obesity and obesity-related chronic diseases. Here, we evaluated the impact of commonly consumed polyphenols, including green tea catechins, especially epigallocatechin gallates, resveratrol and curcumin, on obesity and obesity-related inflammation. Cellular studies demonstrated that these dietary polyphenols reduce viability of adipocytes and proliferation of preadipocytes, suppress adipocyte differentiation and triglyceride accumulation, stimulate lipolysis and fatty acid β-oxidation, and reduce inflammation. Concomitantly, the polyphenols modulate signaling pathways including the adenosine-monophosphate-activated protein kinase, peroxisome proliferator activated receptor γ, CCAAT/enhancer binding protein α, peroxisome proliferator activator receptor gamma activator 1-alpha, sirtuin 1, sterol regulatory element binding protein-1c, uncoupling proteins 1 and 2, and nuclear factor-κB that regulate adipogenesis, antioxidant and anti-inflammatory responses. Animal studies strongly suggest that commonly consumed polyphenols described in this review have a pronounced effect on obesity as shown by lower body weight, fat mass and triglycerides through enhancing energy expenditure and fat utilization, and modulating glucose hemostasis. Limited human studies have been conducted in this area and are inconsistent about the antiobesity impact of dietary polyphenols probably due to the various study designs and lengths, variation among subjects (age, gender, ethnicity), chemical forms of the dietary polyphenols used and confounding factors such as other weight-reducing agents. Future randomized controlled trials are warranted to reconcile the discrepancies between preclinical efficacies and inconclusive clinic outcomes of these polyphenols.